A new approach for the production of multifilament suture - in vitro and in vivo analysis. Issue 18 (12th December 2021) - Rethinam, Senthil; Nallathambi, Gobi; Vijayan, Sumathi; Basaran, Bahri; Mert, Ali; Bayraktar, Oğuz; A., Wilson Aruni
Abstract: We investigated, unique multifilament suture (UMS) was prepared from animal skin fiber (ASF) and cotton fiber (CF), which can be used for external surgeries and wound-healing applications. The distinctive properties of the UMS is that it shows tensile strength of 85.25 ± 0.09 (Mpa), 81.9 ± 0.46 (%) as elongation at break, 7.59 ± 0.26 (kgf) knot strength, 58.95 ± 0.55 (%) of flexibility and water absorption of about 51.03 ± 0.63 (%). In vitro study, performed its biocompatible in nature and in vivo experiments exhibited accelerated suturing and wound-healing properties. Graphical Abstract: UF0001